Insights from Śrīmad Bhāgavatam for mental wellbeing with special reference of Bhikṣu Gītā & Avadhūta Gītā (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In the contemporary era of hyper-connectivity and relentless professional competition, mental health preservation has emerged as a critical global challenge. While modern psychological frameworks provide essential interventions, there is increasing academic interest in the longitudinal wisdom of the Indian Knowledge System (IKS). This paper explores the therapeutic potential of two specific philosophical discourses within the eleventh skandha of the Śrīmad Bhāgavatam: the Bhikṣu Gītā and the Avadhūta Gītā.The research first analyzes the Bhikṣu Gītā, which details the transformation of a miserly Brahmin into a silent ascetic. It emphasizes a cognitive shift from external blame to radical self-accountability. By auditing his "internal dialogue," the protagonist identifies that suffering stems not from external circumstances or Karma, but from an undisciplined mind and the dualistic ideologies of "I-ness" (Ahankara) and "My-ness" (Mamata). The paper argues that renouncing these ego-driven constructs serves as a universal remedy for psychological distress, facilitating equanimity even amidst social persecution.Complementing this internal audit, the Avadhūta Gītā introduces a "universal learning model" through the narrative of Lord Dattatreya. By observing twenty-four "gurus" in nature—such as the patience of the Earth, the non-attachment of the Wind, and the immutability of the Moon—the individual can refine the intellect and optimize the self. This model advocates for humility and the assimilation of wisdom from all sources, regardless of hierarchical status.By synthesizing these ancient perspectives with Aaron Beck’s modern cognitive-behavioral theories on "automatic thoughts," this research demonstrates that the IKS offers a sophisticated "psychological technology." The study concludes that integrating the pedagogical lessons of the Avadhūta with the cognitive discipline of the Bhikṣu provides a sustainable framework for maintaining psychological equilibrium and enhancing the overall quality of life in the 21st century.Research Methodology adopted –This research paper employs a qualitative, hermeneutic, and comparative methodology to explore psychological resilience through the lens of the Indian Knowledge System (IKS). The study utilizes textual analysis of two specific philosophical segments of the Śrīmad Bhāgavatam—the Bhikṣu Gītā and the Avadhūta Gītā—to extract ontological principles regarding mental health and self-regulation. By adopting a narrative analysis of the Ujjayini Brahmin’s transformation, the paper traces the cognitive shift from externalized blame to radical self-accountability. Furthermore, the researcher applies a comparative framework, synthesizing ancient Vedic concepts such as Ahankara (ego) and Vairagya (detachment) with modern Cognitive Behavioral Therapy (CBT) principles, specifically Aaron Beck’s theories on internal dialogue and automatic thoughts. Ultimately, the methodology bridges classical scriptural exegesis with contemporary psychological discourse to propose a sustainable "psychological technology" for the modern era.